Upaya Masyarakat Desa Sembungan dalam Mengatasi Distorsi Harga (Price Distortion) dalam Pengelolaan Wisata Alam (Studi Living Qur’an dan Dakwah) - Ahmad Musyafak (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
The phenomenon of price distortion in the natural tourism area of the Dieng Plateau has become a serious issue that threatens the sustainability of the local tourism industry. Unreasonable price hikes by business actors not only harm tourists economically but also tarnish the image of the destination and disrupt a healthy economic ecosystem. This study aims to examine the strategies employed by the community of Sembungan Village in addressing price distortion through an Islamic values-based approach, using the analytical lens of the Living Qur’an. The research adopts a descriptive qualitative method with a case study approach. Data were collected through field observations, in-depth interviews with the administrators of LMDH Giri Tirto and local business actors, as well as documentation of tourism management regulations. The analysis applies reception theory within the Living Qur’an framework, including cultural, hermeneutic, and aesthetic receptions, to explore the internalization of Qur’anic values in the community’s economic practices. The findings reveal that the people of Sembungan Village enforce strict internal regulations, such as limiting homestay ownership to local residents, setting standardized tariffs, and imposing firm sanctions on violators. Qur’anic values such as honesty, justice, and mutual consent serve as the ethical foundation practiced collectively. These policies have proven effective in maintaining tourist trust, fostering a fair economic ecosystem, and sustaining village tourism. The discussion emphasizes that the Living Qur’an approach bridges religious values with socio-economic practices, particularly in the context of community-based tourism management. Sembungan Village exemplifies the implementation of Qur’anic principles in economic life (muamalah), which are not only normative but also solution-oriented and contextual in addressing contemporary tourism challenges.